Development issues of Bangladesh - Ali, Ashraf; Islam, M. Faizul; Kuddus, Ruhul (Dhaka : University Press, 1996)
Vol. 1 based on the papers presented at a seminar held on August 12, 1995 at the University of Pittsburgh.
Papers presented at a seminar held on August 12, 1995.
v. 1. [no title] -- v. 2. [no title] -- v. 3. Human development and quality of life.
Editors vary.
Includes bibliographical references and index.
Keywords: Rural development -- Bangladesh -- Congresses; Bangladesh -- Economic policy -- Congresses; Bangladesh -- Social policy -- Congresses